2012
DOI: 10.1177/0959683612463100
|View full text |Cite
|
Sign up to set email alerts
|

Holocene variability in hydrology, vegetation, fire, and eolian activity in the Nebraska Sand Hills, USA

Abstract: This study combined multiple aquatic and terrestrial proxies, including diatoms, pollen, grain size, and bulk-sediment chemistry to reconstruct the history of three lake sites located in the central Sand Hills of Nebraska, USA. Long-term changes in effective moisture are evident at all sites, with significant changes occurring at ~6000, ~4000, and ~ 2000 cal. yr BP. Both aquatic and terrestrial indicators suggest that effective moisture was low between 10,000 and ~6000 cal. yr BP, and that this time interval w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Multiproxy studies (Shuman and Marsicek, 2016) for multilatudinal North America also show rapid changes in hydroclimate from approximately 9.3 to 8.2 ka. Studies of interdunal lakes in the NSH (Schmieder et al, 2013;Schmieder et al, 2011) indicate that 10 ka to 6 ka was the driest Holocene period on the Great Plains. This prolonged dry period was followed by shorter drought periods from 4 ka to 3 ka, at 1.5 ka to 1.2 ka, and at 1.0 ka to 700 a (Schmieder et al, 2013;Schmieder et al, 2011).…”
Section: Comparison With Other Climate Proxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiproxy studies (Shuman and Marsicek, 2016) for multilatudinal North America also show rapid changes in hydroclimate from approximately 9.3 to 8.2 ka. Studies of interdunal lakes in the NSH (Schmieder et al, 2013;Schmieder et al, 2011) indicate that 10 ka to 6 ka was the driest Holocene period on the Great Plains. This prolonged dry period was followed by shorter drought periods from 4 ka to 3 ka, at 1.5 ka to 1.2 ka, and at 1.0 ka to 700 a (Schmieder et al, 2013;Schmieder et al, 2011).…”
Section: Comparison With Other Climate Proxiesmentioning
confidence: 99%
“…Studies of interdunal lakes in the NSH (Schmieder et al, 2013;Schmieder et al, 2011) indicate that 10 ka to 6 ka was the driest Holocene period on the Great Plains. This prolonged dry period was followed by shorter drought periods from 4 ka to 3 ka, at 1.5 ka to 1.2 ka, and at 1.0 ka to 700 a (Schmieder et al, 2013;Schmieder et al, 2011). Tree ring data (Cook et al, 2010) also show a dry period for the Great Plains lasting from approximately 1.2 ka to 700 a, and another period of drought lasting from approximately 650 to 550 a, followed by generally wetter conditions.…”
Section: Comparison With Other Climate Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a direct measure of long-term vegetation cover, existing research in the Central Great Plains and prairie grasslands (e.g. Milchunas et al, 1989;Biondini et al, 1998;Forman et al, 2001;Mangan et al, 2004;Stubbendieck, 2008;Grassini et al, 2010;Mangan et al, 2004;Milchunas et al, 1989;Schmieder et al, 2011Schmieder et al, , 2012Stubbendieck, 2008) has identified levels of historical precipitation, grazing, wildfire and land use changes as key factors that affect levels of vegetation. Records of these parameters are gathered from a range of instrumental and archival datasets providing information on precipitation, land use change, wildfire occurrence and regional drought.…”
Section: Approachmentioning
confidence: 99%
“…For example, wetter conditions are implied from cave speleothems in New Mexico and Idaho (Polyak and Asmerom 2001;Lundeen et al 2013) as well as charcoal deposits in alluvial fans in New Mexico (Frechette and Meyer 2009). However, lake and other sediment records in Arizona and Nebraska indicate the opposite with drier conditions present by 4000 BP (Waters and Haynes 2001;Miao et al 2007;Schmieder et al 2012). It is likely then, that the increased variability in ENSO events and climatic patterns caused alternating wet and dry conditions to occur more frequently.…”
Section: Mid To Late Holocene Climate Changementioning
confidence: 99%